Empagliflozin treatment does not affect the hypertensive response to Ang II administration to rats but decreases oxidative stress in the arterial wall, and endothelial and cardiac dysfunction. (25th November 2020) - Bruckert, C; Remila, L; Matsushita, K; Auger, C; Houngue, U; Chaker, A; Park, S; Algara-Suarez, P; Belcastro, E; Jesel, L; Ohlmann, P; Morel, O; et al.
Abstract: Background: Selective sodium-glucose cotransporter 2 (SGLT2) inhibitors have shown cardiovascular protection in type 2 diabetes patients with established cardiovascular disease independently of glycemic control. Angiotensin II (Ang II) and H2O2 have been shown to be strong inducers of the expression of SGLT2 and 1 in endothelial cells promoting oxidative stress and endothelial dysfunction. Purpose: This study examined the cardiovascular protective effect of empagliflozin (empa) in a normoglycemic experimental model of hypertension in the rat. Methods: Male Wistar rats received empa (30 mg/kg/day) provided in the diet for 5 weeks. After 1 week, rats underwent sham surgery (sham rats) or surgery with implantation of an osmotic mini-pump infusing Ang II (0.4 mg/kg/d) for 4 weeks. Systolic blood pressure (SBP) was assessed by sphygmomanometry, the cardiac function using echocardiography, the expression level of target proteins by immunofluorescence staining, and the level of oxidative stress using dihydroethidium staining. Results: Angiotensin II administration increased systolic blood pressure from about 130 to 180 mmHg, which was not affected by the empa treatment. The 4-week Ang II treatment did not significantly affect the systolic cardiac function (cardiac output, left ventricle ejection fraction) but impaired the diastolic function as indicated by a reduced E' and IVRT values, and an increased E/E' value. The Ang II treatment increased significantly the heart and right ventricle weight whereas the left ventricle + septum weight was slightly but not significantly increased. No such functional and structural changes were observed in the Ang II + empa treatment group. An increased immunofluorescence eNOS signal in the endothelium, and a higher level of ROS throughout the aorta wall were observed in the Ang II-treated group, both of which were significantly reduced in the empa + Ang II-treated group. In the Ang II-treated group, the high level of oxidative stress in the aorta was significantly reduced by the AT1 receptor antagonist losartan, the NADPH oxidase inhibitor VAS-2871, the eNOS inhibitor NG-nitro-L-arginine and also to a greater extent by the selective SGLT2 inhibitor empa compared to the dual SGLT1/2 inhibitor sotagliflozin. Conclusion(s): The present findings indicate that although the empa treatment did not affect the hypertensive response of rats to Ang II, the SGLT2 inhibitor prevented the deleterious impact of Ang II on the diastolic cardiac function and remodeling, and the upregulation of eNOS expression and oxidative stress in the aorta wall. Thus, these findings highlight the protective potential of empa on the cardiovascular system in a normoglycemic hypertensive experimental model. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Boehringer Ingelheim Pharma GmbH & Co KG (Biberach an der Riss, Germany)